Synthesis and Characterisation of Vanadium Phosphorous Oxide Catalysts - Looi, Ming Hoong (2004)
The V/P/O catalysts were prepared by using (a) organic method (VPO); (b) via dihydrate phase (VPD) and (c) aqueous method (VPA). The effect of calcination time, preparation method and addition of metal cations as dopants to the physico-chemical properties were studied using nitrogen physisorption measurements, scanning electron microscopy (SEM), X-ray diffraction, inductively coupled plasma (ICP) spectroscopy, redox titration, temperature programmed desorption (TPD) and temperature programmed reduction (TPR). Surface areas of these mesoporous vanadium phosphorous oxides were apparently influenced by the length of calcination time, preparation method and incorporation of metal cations. The changes of surface areas were related to the changes of surface and bulk morphologies as evidenced by SEM. X-ray diffraction revealed that while all of the VIP10 were consisted of predominantly v4+p hase of (V0)2P207,m inority v5+p hase which resumed many crystalline forms made up the remaining portion. Addition of metal cations to the basic matrix resulted in slight loss of crystallinity for V/P/O by VPO method but a huge effect to VIP10 by VPD method which also accompanied by a marked increase in lattice strains. Average oxidation state of vanadium (determined by redox titration) can be altered by (i) increase time of calcinations, (ii) predisposed by the preparation method and (iii) incorporation of metal cations. The persistently lowering of the amount of oxygen atoms that were available thermally until stabilisation at around half a monolayer suggests that the catalytic activity, and hence the conversion of hydrocarbon is stabilised after 100 h. From the extra peak that appeared at higher temperature during TPR by HZ for VIP10 calcined for longer duration, it was postulated that the selective nature of equilibrated VPIO is originated from these oxygen atoms. Based on the above argument, it was suggested that the VPD type of preparation would result in VPIO with more active and selective nature than VPO and VPA. The addition of metal cations to bulk VPO was shown to increase the activity in the order of Zn > VPO (bulk) > Cr > Co and selectivity in the order of Co > Cr > Zn > VPO (bulk). While for VPD the activity and selectivity will be in the order of Co > VPD (bulk) > Cr > Zn and Zn > Cr > VPD (bulk) = Co, respectively